Learning Strategies of Arabic Speaking Skills in Ma'had Hidayatullah Batu: Analysis within the Framework of B.F. Skinner's Behavioristic Theory - M Khaerul Hermawan; Muassomah Muassomah; Laily Fitriani (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to identify speech skills learning strategies, analyze the realization of stimulus, response, and reinforcement, and describe their contribution to improving speech skills. The research uses a descriptive qualitative approach with case studies. Data were collected through participatory observation, semi-structured interviews with curriculum heads, teachers, and students, and documentation. Data analysis used the Miles and Huberman model, with triangulation and peer discussion to guarantee validity. The results showed six integrated strategies: daily conversation, debate, drama, book circles, speeches after Asar, and poetry reading. Each strategy realizes three components of Skinner: stimulus (language commitment, team division, scripting, assignments, rewards); response (spontaneous use, research, argument, memorization, appearance); reinforcement (praise, correction, guidance, evaluation, rewards, peer feedback). Integrated implementation increases students' courage, fluency, confidence, and critical thinking. The theoretical implications reinforce the validity of Skinner's theory with three new findings: social reinforcement of peers is just as effective as extrinsic reinforcement of teachers; the total language environment serves as a continuous discriminatory stimulus; Variations in reinforcement schedules make behaviors more durable. In practical terms, the research offers a model of the integration of six strategies as a holistic learning system. Future research is recommended to conduct quantitative, inter-institutional, and longitudinal studies.